Evaluation of CLASI by paediatric dermatologists and rheumatologists. (1st January 2019) - Kushner, C.J.; Tarazi, M.; Gaffney, R.G.; Feng, R.; Ardalan, K.; Brandling‐Bennett, H.A.; Castelo‐Soccio, L.; Chang, J.C.; Chiu, Y.E.; Gmuca, S.; Hunt, R.D.; Kahn, P.J.; et al.
Summary: The term 'lupus erythematosus' refers to a range of related disorders. As many as 70–80% of lupus patients will develop skin lesions (abnormal patches) at some point during the course of their disease. Types of lupus affecting the skin are collectively known as cutaneous lupus erythematosus (CLE). The Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI) is a tool for classifying how severe the skin symptoms are in people with CLE. Being able to accurately and reliably measure skin lesions is an important way to monitor any improvement or worsening of the disease, which is useful in clinical trials to see if a treatment is working. It is already known that the CLASI is a reliable (accurate) measure in adults, but researchers based in the USA conducted this study to validate the reliability of the CLASI in the pediatric (child) population, where CLE can appear differently than in adults. This validation will allow clinical trials to reliably assess treatment efficacy in CLE. The researchers recruited 11 pediatric patients with active CLE, 6 dermatologists, and 6 rheumatologists to attend a one‐day event at the University of Pennsylvania. Physicians were trained to use the CLASI as well as another scoring system called the Physician Global Assessment (PGA) to allow for comparison. Physicians (doctors) individually rated all patients using both tools. Each physician reassessed two randomly selected patients. CLASI proved to be a reliable and valid measurement tool and superior to the PGA for pediatric CLE, and the researchers conclude that it can be used in future clinical trials.